(untitled) (Research, Society and Development, 2021)
The biodiverse agroforestry systems (BAS) combine fruitful or woody tree species, with agricultural crops and / or animal husbandry, in the same area. For the farmer who owns it, these systems improve the quality of economic, social and environmental life, as they provide sustainable forms of food production, food security, in addition to environmental preservation. The study presents the financial viability analysis of two models of agroforestry systems implemented in the municipality of Dourados, MS. The research aimed to provide subsidies to family farmers for the implementation of SAF’s. The crops of economic interest selected for the composition of the implanted SAF’s were: BAS1- coffee, pineapple, corn, beans; BAS2 - pupunha palm, banana, pineapple, corn, beans, in addition to nine tree species for both BAS: acerola, soursop, guava, pitanga, aroeira, guaritá, ipê, canafístula and pigeon breast, each BAS had one hectare . For planning and elaboration of the systems, the AmazonSAF spreadsheet was used, where data of income and expenses were inserted, which reflect the reality of family farming, verifying profitability over 20 years. Both BAS was financially viable, as the Net Present Value of BAS 1 was R 11,018.24 and BAS 2 was R 40,377.04. The latter presented itself slightly as the most profitable, since its Benefit/Cost ratio was 1.2 and the payback was 9 years, different from BAS 1, whose RB/C was 1.1 and the payback was 10 years. The financial viability of both BAS 1, with coffee as the main crop, and BAS 2, with pupunha and banana hearts, was confirmed, in order to guarantee to the rural producer that, if well planned and monitored, these systems showed good conditions for food production and income generation. In addition, they become possible solutions for sustainable agriculture, valuing and using natural resources wisely.